Empowering Women Through the Sekoper Cinta Program in an Effort to Build Family Welfare based on Community Civics Perspective - Wafa Khairunisa; Ema Suryanti; Muhammad Rafsan Wiratama (International Journal of Social Service and Research (IJSSR), 2023)
Sekoper Cinta program is one of the flagship programs of the West Java Provincial Government which has the goal of increasing the independence of a woman through participatory empowerment activities and character education by implementing non-formal education according to West Java Governor Decree Number 420.05/Kep.1224/Yanbangsos/2018 concerning Organizing Team for Sekolah Perempuan Capai Impian dan Cita-Cita (Sekoper Cinta). This study aims to find out Sekoper Cinta program on family welfare based on community civics perspectives. This study uses a qualitative approach with the method of reviewing literature, the data analysis technique used is reading sources from books, journals and previous research that are most relevant, noting important matters, analyzing problems, and including all sources used. While the data analysis technique used by the researcher is through three stages including data reduction, data display, and drawing conclusions and verification. The results of the research show that the Sekoper Cinta program viewed from the perspective of community civics functions as a means of understanding oneself, educating children well, and can open up business opportunities in the economic side. Sekoper Cinta also plays a role as a forum for women to interact, communicate, share knowledge, and experience in order to get an increase in the quality of life and improve family welfare.